2015
DOI: 10.1186/s12958-015-0028-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased paternal age on sperm quality, reproductive outcome and associated epigenetic risks to offspring

Abstract: Over the last decade, there has been a significant increase in average paternal age when the first child is conceived, either due to increased life expectancy, widespread use of contraception, late marriages and other factors. While the effect of maternal ageing on fertilization and reproduction is well known and several studies have shown that women over 35 years have a higher risk of infertility, pregnancy complications, spontaneous abortion, congenital anomalies, and perinatal complications. The effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
254
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(276 citation statements)
references
References 276 publications
(302 reference statements)
8
254
2
12
Order By: Relevance
“…Firstly, the 12.0% prevalence of azoospermia in the overall study group accords with the 10% -15% quoted by Gudeloglu and colleague [7] but much less than the 40% reported by Bashed et al [24] in Bangladesh. Earlier and recent studies have also shown decline in some semen quality with age [25] [26] such as lower ejaculate volume and sperm motility [27] [28] and increased paternal age with sperm quality [29]. There appears to be a phenomenon of gradual reduction in sperm quality of Africans as reported in a recent study [30].…”
Section: Discussionmentioning
confidence: 72%
“…Firstly, the 12.0% prevalence of azoospermia in the overall study group accords with the 10% -15% quoted by Gudeloglu and colleague [7] but much less than the 40% reported by Bashed et al [24] in Bangladesh. Earlier and recent studies have also shown decline in some semen quality with age [25] [26] such as lower ejaculate volume and sperm motility [27] [28] and increased paternal age with sperm quality [29]. There appears to be a phenomenon of gradual reduction in sperm quality of Africans as reported in a recent study [30].…”
Section: Discussionmentioning
confidence: 72%
“…As expected, there exists a strong correlation between maternal and paternal age at birth in VOLUME 53 __ OCTOBER 15, 2016 EDITORIAL India (r=0.72, P<0.0001) suggesting substantial residual confounding at the family/household level including support for a strong presence of assortative mating [11]. While it has been hypothesized that there may be mechanisms where paternal age could affect birth outcomes [17] (e.g., quality of sperm, epigenetic or DNA changes), it would mainly be observed among older males (>50 years) [18]. In the absence of any biologic mechanisms for younger fathers, we should expect the maternal effects to be much larger at younger ages.…”
Section: Resultsmentioning
confidence: 99%
“…There were negative associations between increasing paternal age and reduction in testicular volume up to 31% and reduction testicular size. 10 This decreased testicular volume is also attributed to the decrease in number of spermatogenic and Sertoli cells. Histologically, degenerative changes in germinal epithelium and decreased number of Leydig cells can be observed.…”
Section: Aging and Male Infertilitymentioning
confidence: 99%
“…Further, it has been shown that luteinizing hormone (LH) levels have a reverse relationship with serum testosterone levels in the case of aging. 10 The most scientists approve the free radicals/ oxidative stress theory that underlying many conditions related to aging process. This theory states that the age-related accumulation of free radicals and superoxide leads to damage of macromolecular components such as carbohydrates, lipids, proteins and nucleic acids which are the building blocks of cellular structure.…”
Section: Aging and Male Infertilitymentioning
confidence: 99%